Effect of surface modification of orthodontic appliances on biofilm adhesion – A systematic review: Surface modified archwires effect on biofilm adhesion - SR - Sivakumar, Nishanth; Srinivasan, Dilip; Devasahayam, Davis; Kannan, Ravi (International Journal of Psychosocial Rehabilitation, 2024)
im: To evaluate the effect of various coatings and its effect on the microbial adhesion on the orthodontic appliance Materials and methods: A systematic review is being conducted using the available electronic data bases which were analysing the microbial adhesion after coating of appliances against uncoated appliances. Due to the paucity of in vivo studies, invitro studies also were considered. Data extraction was performed from each study and the results were tabulated. Results: 8 studies which fulfilled the inclusion criteria were selected. Risk of bias assessment showed a medium to high risk of bias for most of the studies. The effect of various coatings on the appliance was analysed. Conclusion: Roughness is an important but not the only factor for microbial adhesion. The property of the coatings also plays an important role. More high evidence studies are required to obtain more reliable results.